Le Conseil national de sécurité et la politique sud-africaine des États-Unis de 1969 à 1976. - David, Charles (Études internationales, 1981)
This article examines the performance of the U.S. National Security Council as a policy-making body vis-à-vis the southern African conflict under the Nixon and Ford Administrations. It discusses and verifies the hypothesis that the institutionalized System of the NSC gives the President a way of seriously improving his policies, by analyzing (within a structured and formalized framework) the range of options and alternatives, free of negative bureaucratic influences. Furthermore, it shows the impact that the presidential decisions had over the orientation of the southern African conflict from 1969 to 1976.